2021
DOI: 10.3390/agronomy11010170
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Transcription Factor GmTGA15 Enhances Drought Tolerance in Transgenic Soybean Hairy Roots and Arabidopsis Plants

Abstract: Soybean (Glycine max) is one of the important oil crops worldwide. In recent years, environmental stresses such as drought and soil salinization have severely deteriorated soybean yield and quality. We investigated the overexpression of the transcription factor GmTGA15 in response to drought stress in transgenic soybean hairy roots and Arabidopsis plants. The results of quantitative real time polymerase chain reaction (qRT-PCR) analyses showed that GmTGA15 was greatly induced by salt, PEG6000, salicylic acid (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Lipid peroxidation in the cell membranes is reported to be one of the most challenging and detrimental effects of water stress on the membranes of all the cells exposed to varied degree of stress [48]. Chen and colleagues mentioned that MDA content increased in soybean wild type plants in response to drought stress [49].…”
Section: Resultsmentioning
confidence: 99%
“…Lipid peroxidation in the cell membranes is reported to be one of the most challenging and detrimental effects of water stress on the membranes of all the cells exposed to varied degree of stress [48]. Chen and colleagues mentioned that MDA content increased in soybean wild type plants in response to drought stress [49].…”
Section: Resultsmentioning
confidence: 99%
“…These results indicated that JA-responsive IbMYB116 promotes plant tolerance to drought stress by modulating the JA response. Another JA-responsive transcription factor, GmTGA15, showed a similar effect on drought tolerance in soybean [95]. Overexpression of GmTGA15 promoted the accumulation of proline and improved tolerance to drought stress in soybean.…”
Section: Ja and Drought Stressmentioning
confidence: 94%
“…It was also found in another study that the GA 2-Oxidase gene ( OsGA2ox ) was found to improve rice drought resistance [ 89 ]. In a recent study, soybean TF GmTGA15 was shown to be overexpressed in plants with low moisture content [ 17 ].…”
Section: Drought-responsive Genes Are Regulated By Plant Hormonesmentioning
confidence: 99%
“…Low amounts of SA boost plant antioxidant capability, but greater levels can kill cells or make plants more vulnerable to abiotic stress [ 11 ]. SA stimulates genes with roles in the production of secondary metabolites, chaperones, organic acids, and heat shock proteins [ 16 , 17 ]. Cell elongation, vascular tissue improvement, and apical dominance are all known impacts of indole-3-acetic acid on plant elongation and development [ 18 ].…”
Section: Introductionmentioning
confidence: 99%